Sustainable Reflexivities on Perennial Philosophy and Christian Education Management - Apriedo, Sandro; Septiana, Listia; Anugrahani, Callista; Gomor, Obertina; Silipta (Kirana Publisher (KNPub), 2023)
The background of this research is the authors' anxiety in the midst of accelerating times in the education space as if to announce that the old educational values are outdated and irrelevant values. This thoughts are more to the prioritization of constructive philosophy, or something that is deconstructed. Meanwhile, the context of education cannot be universalized into one even though the regulations in education in a country cover the whole. Old values are meaningful and timeless values that are timeless. This kind of thinking is a thought that departs from the philosophy of perennialism. This is qualitative research with data search through data sourced from journals as previous research as a secondary source. Results show that the philosophy of perennialism here serves as an analytical and differentiating tool to look back at the philosophy of constructionism as a criticism as well as a realization for the world of education in the form of the importance of maintaining existing or embedded values so far.